LITERARY ADAPTATIONS IN PORTUGUESE AS A FOREIGN LANGUAGE TEACHING: A CASE STUDY - Machado, Ana Maria (2019)
The “Literature in Portuguese Foreign Language Teaching” project aims to study literature’s role in the first stage of Portuguese as a Foreign Language teaching. Apart from the selection of literary texts for beginner and elementary levels (A1 and A2 respectively), the project also includes simplified versions of short stories that are relevant to this teaching context due to heritage and interculturality reasons. At A1 and A2 teaching levels, the process for simplifying a text should not be limited to literary adaptation, reason why our simplification took into account the criteria used by graded readers editors and in the few existing adaptations in Portugal. Due to the lack of simplified versions of literary texts in those levels of Portuguese teaching, it is important to share and discuss the experience gathered with the simplification of O Senhor Ventura, by Miguel Torga (1943/1985). This article reflects on the results of its’ use in different formal education contexts and on its’ implications for the definition of simplification criteria.